Ropinirole, a New ALS Drug Candidate Developed Using iPSCs - Okano, Hideyuki; Yasuda, Daisuke; Fujimori, Koki; Morimoto, Satoru; Takahashi, Shinichi (Trends in pharmacological sciences (Regular ed.), 2020)
Induced pluripotent stem cells (iPSCs) are increasingly used in the study of disease mechanisms and the development of effective disease-modifying therapies for neurodegenerative diseases, including amyotrophic lateral sclerosis (ALS). Recently, three candidate anti-ALS drugs – ropinirole (ROPI), retigabine, and bosutinib – have been identified in iPSC-based drug screens and are now being evaluated in clinical trials for safety and effectiveness. We review the preclinical data, clinical research design, and rationale for ROPI as an anti-ALS drug candidate compared with those of the other two drugs. We also discuss the use of iPSCs for understanding and monitoring treatment response as well as for new insights into the development of new drugs and therapeutic interventions for major neurodegenerative diseases. iPSC-based drug discovery is a promising technology for developing novel therapeutics for neurodegenerative diseases lacking useful disease models, such as amyotrophic lateral sclerosis (ALS).Ropinirole, retigabine, and bosutinib were identified as candidate therapeutic agents for ALS by the combination of iPSC-based drug discovery and drug repositioning.The potential anti-ALS mechanism of ropinirole is independent of antioxidant activity, rescue of mitochondria, reduction of stress granules, and abnormal proteins such as phosphorylated TDP-43 and FUS, and dopamine D2 receptor (D2R) agonism.Retigabine inhibits the hyperexcitability of motor neurons in ALS and bosutinib prompts autophagy and reduces abnormal proteins such as SOD-1 and phosphorylated TDP-43 via the Src/c-Abl pathway in motor neurons in ALS.Stratification of ALS, personalized medicine strategies, and the identification of common mechanisms with other neurodegenerative diseases are key aspects in the development of ALS therapies.